First Series Using Ultrasonic Propulsion and Burst Wave Lithotripsy to Treat Ureteral Stones. Issue 5 (1st November 2022) - Hall, M. Kennedy; Thiel, Jeff; Dunmire, Barbrina; Samson, Patrick C.; Kessler, Ross; Sunaryo, Peter; Sweet, Robert M.; Metzler, Ian S.; Chang, Helena C.; Gunn, Martin; Dighe, Manjiri; Anderson, Layla; et al.
Abstract : Purpose: Our goal was to test transcutaneous focused ultrasound in the form of ultrasonic propulsion and burst wave lithotripsy to reposition ureteral stones and facilitate passage in awake subjects. Materials and Methods: Adult subjects with a diagnosed proximal or distal ureteral stone were prospectively recruited. Ultrasonic propulsion alone or with burst wave lithotripsy was administered by a handheld transducer to awake, unanesthetized subjects. Efficacy outcomes included stone motion, stone passage, and pain relief. Safety outcome was the reporting of associated anticipated or adverse events. Results: Twenty-nine subjects received either ultrasonic propulsion alone (n = 16) or with burst wave lithotripsy bursts (n = 13), and stone motion was observed in 19 (66%). The stone passed in 18 (86%) of the 21 distal ureteral stone cases with at least 2 weeks follow‐up in an average of 3.9±4.9 days post-procedure. Fragmentation was observed in 7 of the burst wave lithotripsy cases. All subjects tolerated the procedure with average pain scores (0-10) dropping from 2.1±2.3 to 1.6±2.0 ( P = .03). Anticipated events were limited to hematuria on initial urination post-procedure and mild pain. In total, 7 subjects had associated discomfort with only 2.2% (18 of 820) propulsion bursts. Conclusions: This study supports the efficacy and safety of using ultrasonic propulsion and burst wave lithotripsy in awake subjects to reposition and break ureteral stones to relieve pain and facilitate passage.